2000
DOI: 10.1111/j.1540-8159.2000.tb00799.x
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Structure of Electrocardiographic Waveform During Prolonged Ventricular Fibrillation in Swine

Abstract: Ventricular fibrillation (VF) is the most common arrhythmia causing sudden cardiac death. However, the likelihood of successful defibrillation declines with increasing duration of VF. Because the morphology of the electrocardiogram (ECG) waveform during VF also changes with time, this study examined a new measure that describes the VF waveform and distinguishes between early and late VF. Surface ECG recordings were digitized at 200 samples/s from nine swine with induced VF. A new measure called the scaling exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 24 publications
1
32
0
Order By: Relevance
“…The scaling exponent (ScE), LAC, and Hurst exponent have been well characterized in a large group of swine in earlier experimental work [7,9,14]. They show an increase in the fractal dimension over time.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The scaling exponent (ScE), LAC, and Hurst exponent have been well characterized in a large group of swine in earlier experimental work [7,9,14]. They show an increase in the fractal dimension over time.…”
Section: Discussionmentioning
confidence: 96%
“…Earlier laboratory studies have demonstrated that VF waveform analysis methods can provide an estimate of the duration of VF from the recorded electrocardiogram for use in treatment algorithms [4][5][6][7][8][9][10]. These methods exploit the two main features of the VF waveform, namely, frequency and roughness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This measure shows how the signal under consideration differs from the random one, which is characterized by ScE≈2 [6]. We estimated ScE as described previously [1,3]. Briefly, we calculated function L (k) for lag k = 1−1024.…”
Section: Methodsmentioning
confidence: 99%
“…Many attempts have been made to use the measures based on the ECG waveform in frequency and time domain as a means of assessing VF duration for optimization of the resuscitation strategies [1][2][3][4][5][6][7][8][9][10][11]. Accumulated clinical and laboratory data [1][2][3][4][5][6][7][8][9][10][11] have shown that these ECG waveform-based measures, or combinations of these measures, can help to predict the likelihood of the successful countershock therapy in cardiac arrest patients. However, analysis of ECG during VF can be confounded by extra-cardiac phenomena.…”
Section: Introductionmentioning
confidence: 99%